Islamic social finance for sustainable economic growth in Bangladesh - Hossain, Mohammad Enayet; Mahadi, Nur Farhah; Haron, Razali; Mohd Nor, Rizal; Yousuf, Md. Abu (IIUM Institute of Islamic Banking and Finance, 2025)
Islamic social finance (ISF) instruments such as Zakat, Waqf, Sadaqah, and Islamic Microfinance play a vital role in enhancing the standard of living and addressing financial difficulties the impacted community faces during challenging times. This paper attempts to analyze the role of Islamic social finance in sustainable economic growth in Bangladesh; specifically, it examines the role of Zakat and Islamic Microfinance. Zakat and Islamic microfinance are crucial in achieving sustainable economic growth in Bangladesh by offering targeted financial solutions for the underprivileged. This study used a quantitative research method, and data was collected from the capital city of Bangladesh. Data collection used a questionnaire containing 20 questions that utilized a Likert scale and aimed to assess independent and dependent variables. The research used SmartPLS version 4 and SPSS version 25 for extensive data analysis. The findings of this study illustrate that Zakat and Islamic microfinance are significantly positive in terms of sustainable economic growth in Bangladesh. Data sampling is one of this study's research limitations because it only collected data from Bangladesh's capital city. To conduct the rigorous analysis, data should come from other sources.